Catheter Displacement into Inferior Epigastric Vein Causing Local Phlebitis and Cellulitis - Noriko Hattori; Hidenori Hattori; Kazushi Takahashi; Norihiro Suzuki; Kazuo Kishi (Case Reports in Medicine)
Catheter insertion for intravenous hyperalimentation is a commonly and widely used clinical technique. When compared with the incidence of complications associated with insertions into the internal jugular vein or the subclavian vein, complications associated with insertions into the femoral vein are less frequent. In this paper, we describe a very rare complication of femoral vein catheter insertion—namely, catheter displacement into the inferior epigastric vein.